Diagnóstico ambiental de metais e organoclorados em córregos adjacentes a áreas de cultivo de cana-de-açúcar (Estado de São Paulo, Brasil) - Corbi, Juliano José; Strixino, Susana Trivinho; Santos, Ademir dos [UNESP]; Del Grande, Marcelo (Sociedade Brasileira de Química, 2006)
Sugar cane cultivation in the State of São Paulo has expanded in the last years, with an annual production of 200 10(6) t in an area of 2.5 10(6) hectares. The use of herbicides, pesticides and fertilizers in sugar cane plantations, together with deforestation of riparian vegetation, have caused impacts on the hydric resources of the adjacent areas. The aim of this work is to evaluate the influence of sugar cane plantations on streams in the central region of the State of São Paulo, studying 16 organochlorinated compounds and 7 metals (Cu, Fe, Cd, Zn, Mn, Cr and Ni) found in the sediments of 11 streams. The results show that there is a higher concentration of metals and organochlorinated compounds in streams without riparian vegetation when compared to forested areas.
Environmental diagnostic of metals and organochlorinated compounds in streams near sugar cane plantations activity (São Paulo State, Brazil)
Keywords: sugar cane cultivation; heavy metals; organochlorinated compounds